Nunca supe decir no Crónicas 8 - Alzate, Gabriel Jaime (Editorial Bonaventuriana, Universidad de San Buenaventura Cali., 2020)
The Faculty of Psychology of the University of San Buenaventura Cali, has undertaken for several years the task of accompanying our students of Writing Workshop I in the exercise of the materialization of a chronicle to capture life through letters and for those who read it, to understand from another point of view a reality that traps, tears and hurts, but that transforms our thinking and our being. This with the dreamy pretension that our students launch themselves into the void and discover the richness of writing as an escape from pleasure, but also as an act to represent the voices that accompany the multiple faces of human life, an exercise similar to painting or putting music to a voice.